ORGANIZATION OF PUBLIC SPORTS ACTIVITIES AMONG THE POPULATION: ORGANIZATION OF PUBLIC SPORTS ACTIVITIES AMONG THE POPULATION - ismatov, abduqodir (Физическое воспитание, спорт и здоровье, 2022)
In this article, sports facilities play an important role in the success of mass sports in residential areas. Widespread introduction of a healthy lifestyle and further development of mass sports, as well as the creation of modern conditions for regular physical education and mass sports.